Analisis Kelayakan E-Modul Perubahan Lingkungan: Integrasi Video dan Project Based Learning Di SMA - Deden Aqil; Adeng Hudaya; M Ramadona (Universitas Indraprasta PGRI, 2025)
The low level of environmental sensitivity among high school students highlights the need to improve the quality of learning. One approach is to transform teaching materials from textual formats into digital ones in the form of e-modules. This study aims to develop a Project-Based Learning (PjBL)-based e-module on environmental change materials, supplemented with videos as a learning medium, that is suitable for use by 10th-grade high school students. The research was conducted from October 2024 to January 2025. The research method used was a qualitative approach through Research and Development (RnD) with the ADDIE model. The research instruments included questionnaires to assess the feasibility of the e-module, evaluated by media, learning, content, and language experts, as well as responses from students and teachers to determine the feasibility of the developed e-module. Based on expert evaluations, the developed e-module was found to be in the